How Satisfied Is The Samarinda Community With Parking Services - Sari, Ade Risna (Journal of Management, 2023)
The study is concerned with public satisfaction with alternate parking options accessible near the Samarinda Wisatadi Object. Because of the high number of visitors or visitors of the Tourist Objects who come to the tourist spot without knowing the actual number, the population of this study is uncertain. As a result, the sample was tallied using the lemeshow formula, yielding at least 88 responses. The research method employed is quantitative, with data collected using questionnaires and supplemented with interview results. Simple regression algorithms are utilized for data analysis. The research findings indicate that the full hypothesis has been accepted because the test results are both positive and significant